Challenges Facing Special Educational Needs (SEN) Teachers when Communicating with the Parents of Children with Disabilities (CWDs) from the Perspective of Teachers - Thamer Hassan Al-Ahmed (SAGE Open)
This study aims to identify the challenges faced by special educational needs (SEN) teachers when communicating with the parents of children with disabilities (CWDs). To achieve its objectives, this research employs a descriptive approach founded on the results of 152 electronic surveys completed by male and female SEN teachers from the Makkah region of the Kingdom of Saudi Arabia (KSA). The results indicate an average level of difficulty of 3.20 for all dimensions. The first dimension (challenges related to parents) reported a mean of 3.44; while the second dimension (challenges related to teachers) produced a mean of 3.08; and the final dimension (challenges related to the educational institutions) recorded a mean of 3.06. The research did not identify any statistically significant differences concerning the impact of sex or experience variables across any of the three dimensions. Furthermore, the variable concerning academic qualification demonstrated no significant impact on the challenges related to teachers and educational institutions; however, this variable significantly impacted the challenges related to parents. Correspondingly, although the variable concerning training courses had no significant impact on the challenges related to parents and teachers, it did present challenges to educational institutions. Based on these findings, this study recommends that the parents of CWDs and SEN teachers should receive additional guidance and training concerning the contribution of effective communication to the success of the educational process. Additionally, this research recommends that the parents of CWDs should participate in regular, scheduled meetings with SEN teachers (under the supervision of school administration teams).